2019
DOI: 10.1002/ece3.5052
|View full text |Cite
|
Sign up to set email alerts
|

The role of recombination, niche‐specific gene pools and flexible genomes in the ecological speciation of bacteria

Abstract: Bacteria diversify into genetic clusters analogous to those observed in sexual eukaryotes, but the definition of bacterial species is an ongoing problem. Recent work has focused on adaptation to distinct ecological niches as the main driver of clustering, but there remains debate about the role of recombination in that process. One view is that homologous recombination occurs too rarely for gene flow to constrain divergent selection. Another view is that homologous recombination is frequent enough in many bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…For instance, in ISL2, two COGs shared by all subpopulations and subject to strong selective constraints (means d N /d S < 0.19) were related to phosphonate utilization, which could suggest adaptation to low‐phosphate environments (Feingersch et al., 2012). Recently, Schmutzer and Barraclough (2019) suggested that, in the presence of gene fluxes among diverging populations, the concentration of locally adapted genes in a reduced number of loci could be favoured, as it would (a) reduce the negative impact of insertions along the genome of horizontally transferred genes; and (b) increase the relative efficacy of selection on a few “mega” loci compared to many dispersed loci of reduced effect. Thus, ISL1, ISL2 and ISL2.1 might concentrate “flexible” genes that are essential for all these clades.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in ISL2, two COGs shared by all subpopulations and subject to strong selective constraints (means d N /d S < 0.19) were related to phosphonate utilization, which could suggest adaptation to low‐phosphate environments (Feingersch et al., 2012). Recently, Schmutzer and Barraclough (2019) suggested that, in the presence of gene fluxes among diverging populations, the concentration of locally adapted genes in a reduced number of loci could be favoured, as it would (a) reduce the negative impact of insertions along the genome of horizontally transferred genes; and (b) increase the relative efficacy of selection on a few “mega” loci compared to many dispersed loci of reduced effect. Thus, ISL1, ISL2 and ISL2.1 might concentrate “flexible” genes that are essential for all these clades.…”
Section: Discussionmentioning
confidence: 99%
“…Much literature on bacterial speciation has addressed how barriers to recombination could drive bacterial speciation (e.g. Fraser et al ., 2007; Polz et al ., 2013; Schmutzer & Barraclough, 2019). Most importantly, recombination seems to decrease in frequency with greater genetic divergence between individuals (e.g.…”
Section: Speciation In Prokaryotesmentioning
confidence: 99%
“…Vulic, Lenski & Radman, 1999). Simulations suggest that reduced recombination may be important in those clades with relatively high recombination rates (Schmutzer & Barraclough, 2019). However, this mechanism may not apply to prokaryotic lineages that have little or no homologous recombination, including archaeans and many bacterial species (e.g.…”
Section: Speciation In Prokaryotesmentioning
confidence: 99%
“…Cohan & Perry hypothesized that periodic selective sweeps reduce genetic variation between the genomes of organisms specialized to certain ecological niches, increasing the differences between these ecotypes and the rest of the named species [69]. However, other authors emphasize the role of recombination in bacterial divergence which allows for gene-specific sweeps [70].…”
Section: Discussionmentioning
confidence: 99%